CMOS-based Instrumentation Amplifier for Biomedical Application - Ng Wee, Wei Ki; Mat Jubadi, Warsuzarina (Evolution in Electrical and Electronic Engineering, 2021)
An instrumentation amplifier is normally used for the measurement of low-frequency signals including electrocardiogram (ECG), brain signals, nerve synapses pulses, etc. Biomedical signals usually are very weak due to low amplitude. An instrumentation amplifier which practically applied in biomedical applications is designed due to its numerous advantages such as gain can be adjusted easily by a single control without changing the whole structure and its common-mode rejection ratio (CMRR) is high. This project proposed a three op-amp instrumentation amplifier by using three two-stage complementary metal-oxide-semiconductor (CMOS) op-amp. This project is designed and simulated with Cadence Software using 130 nm CMOS technology. The gain of the proposed amplifier for pre-layout simulation is 64.15 dB with input-referred noise of 10.41 µ(V/√Hz) and power dissipation of 115.6 µW and a CMRR of 107.25 dB. The gain of the amplifier for post-layout simulation is 63.69 dB with input-referred noise of 10.52 µ(V/√Hz), the power dissipation of 115.6µ W, and CMRR of 100.39 dB. Apart from that, the amplifier is designed with a size layout of 5.25 x 104 µm2.